Mutations alter pll gene promoter from constitutive to inducible, coffering palmately lobed leaf trait of melon - Yong, LiangMin; Dai, Wenting; Zhang, Xuan; Zhang, Qiang (Frontiers in Plant Physiology, 2024)
The leaves of the common melon are approximately round and uncut. A natural mutant of melon named bm7, which has palmately-lobed leaves. We found that bm7 plants were more conducive to increasing planting density and achieving higher yields, and showed better disease resistance. Therefore, the germplasm resources of muskmelon split leaves have the potential of application. Previous study showed that the palmately-lobed leaf trait was controlled by a single recessive gene, pll (numbered MELO3C010784). By cloning and sequencing the pll genes of Jiashi (wide-type) and bm7 (mutant) plants, we noticed that there was no mutation in this gene, but its expression level in bm7 was far below than that in Jiashi. The silencing of pll gene with virus induced gene silencing (VIGS) confers palmately-lobed leaf trait of Jiashi plants. We found three mutations in the pll gene promoter of bm7 plants, located at 373, 493, 506 bp upstream the translation initiation codon. Then, we had found the pll gene promoter activity of bm7 was significantly lower than that of Jiashi. In addition, the expression level and promoter activity of pll gene in Jiashi plants were not affected by environmental factors, but in bm7 plants, the expression level and promoter activity of pll gene, all decreased with the increase in light intensity and/or temperature. All the results indicated that the mutations convert the pll gene promoter from constitutive to inducible, and results in significantly reduced expression of pll gene, conferring the palmately-lobed leaf trait of melon.